2021
DOI: 10.3390/en14113045
|View full text |Cite
|
Sign up to set email alerts
|

On the Evaluation of Interfacial Tension (IFT) of CO2–Paraffin System for Enhanced Oil Recovery Process: Comparison of Empirical Correlations, Soft Computing Approaches, and Parachor Model

Abstract: Carbon dioxide-based enhanced oil-recovery (CO2-EOR) processes have gained considerable interest among other EOR methods. In this paper, based on the molecular weight of paraffins (n-alkanes), pressure, and temperature, the magnitude of CO2–n-alkanes interfacial tension (IFT) was determined by utilizing soft computing and mathematical modeling approaches, namely: (i) radial basis function (RBF) neural network (optimized by genetic algorithm (GA), gravitational search algorithm (GSA), imperialist competitive al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…Surfactant addition not only improves foam stability, but it also alters wettability, which speeds up oil flow by reducing capillary forces. 22 During foam flooding in porous media, the production of thin liquid coatings known as lamellas blocks the gas phase flow in some areas. Foam stability is provided by the ability of hydrophilic surfactant molecules to adsorb on the gas–water interface, while foam movement is regulated by surfactant-generated lamellae in reservoir micropores.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant addition not only improves foam stability, but it also alters wettability, which speeds up oil flow by reducing capillary forces. 22 During foam flooding in porous media, the production of thin liquid coatings known as lamellas blocks the gas phase flow in some areas. Foam stability is provided by the ability of hydrophilic surfactant molecules to adsorb on the gas–water interface, while foam movement is regulated by surfactant-generated lamellae in reservoir micropores.…”
Section: Introductionmentioning
confidence: 99%
“…Injection of CO 2 presents an effective enhanced oil recovery (EOR) approach for several reasons such as low CO 2miscibility pressure, CO 2 sequestration, oil swelling, and viscosity reduction (Wei et al, 2017;Hafez et al, 2021;Wang et al, 2022). CO 2 injection can improve the oil production from depleted reservoirs through different mechanisms such as mobilizing the residual oil, pressurizing the reservoir, and reducing the interfacial forces between oil and CO 2 (Bennion and Bachu, 2006;Perera et al, 2016;Rezaei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of CO 2 flooding can be reduced by several phenomena such as gravity override and viscous fingering, due to the considerable differences between the density/viscosity of the crude oil and CO 2 (Lake, 1989;Rezaei et al, 2021). Therefore, poor sweep efficiency can be induced during CO 2 flooding, leading to fast CO 2 breakthrough and low oil recovery (Chang and Grigg, 1999;Le et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They used 879 datasets gathered from the literature and showed that their model has an AAPRE of 4.42%. 45 …”
Section: Introductionmentioning
confidence: 99%
“…They used 879 datasets gathered from the literature and showed that their model has an AAPRE of 4.42%. 45 In the literature, some methods were used to determine the P b . However, the previous models and correlations have some limitations, such as lack of accuracy and a need for computer software such as machine learning and deep learning (LSTM) approaches.…”
Section: Introductionmentioning
confidence: 99%